Thế giới nhân vật trong truyện ngắn Việt Nam và nước ngoài ở chương trình THPT Khóa luận tốt nghiệp - Phạm Thị Bích Thủy (2017)
Giới thiệu thế giới nhân vật trong truyện ngắn Việt Nam và trong truyện ngắn nước ngoài ở chương trình THPT.